Diagnosis of Frasier’s Syndrome in a limited Resources Center: A Case Report - Axler Jean Paul; Dieuguens Louis; Ansly Jefferson Desravines; Raema Mimrod Jean; Alfadler Jean Baptiste; Jean Henold Buteau; Wislet Andre (Medical Research and Its Applications Vol. 9, 2024)
Background: Frasier syndrome is a rare genetic nephropathy characterized by the presence of progressive glomerulopathy with proteinuria associated with male pseudo-hermaphroditism. The symptomatology evolves into a treatment-resistant nephrotic syndrome that progressively leads to end-stage renal failure during the first two decades of the child’s life. Aim: This case study described a picture of a young boy where the clinical suspicion context reminded the Frasier syndrome. To our knowledge, this case is the first described in Haiti. Case Study: We report a case of a 19-year-old young phenotypically male, born with a genital anomaly, who was seen on referral at the nephrology/dialysis unit of the internal medicine department of the State University Hospital of Haiti for evaluation and follow-up. Insidious progression of symptoms had occurred over 3 years. He had four sets of renal labs obtained throughout his three months of outpatient follow-up, all of which revealed decreased renal function. An ultrasound reveals bilateral cryptorchidism in the inguinal canal as well as the existence of functional ovaries with dispersed, variable-sized follicles in the parenchyma. Therefore, we came to the diagnosis of end-stage renal failure by progressive glomerulopathy in the context of Frasier’s syndrome based on these anamnestic, clinical, and paraclinical observations. Conclusion: With any clinical picture consisting of genital anomalies at birth, renal symptomatology during childhood and the diagnosis of renal failure during adolescence, rare genetic nephropathies, such as Frasier syndrome must be considered. In low-income settings such as ours, where genetic technology is not always available, the diagnosis of Frasier syndrome should be considered in any child with developmental abnormalities of the external genitalia presenting with isolated proteinuria and/or signs of impaired renal function during childhood or adolescence.